2005
DOI: 10.1177/1527154405275884
|View full text |Cite
|
Sign up to set email alerts
|

State Policies Regarding Nursing Delegation and Medication Administration in Child Care Settings: A Case Study

Abstract: Medication administration is an essential component of quality child care, and nurses play a central role in assuring high-quality training of child care providers. Through key informant interviews and review of public documents, this case study explored the development of state statutes and regulations for medication administration training of child care providers in the state of Connecticut, nursing liability issues related to the definition of this activity, and the role of the Connecticut State Board of Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 2 publications
0
15
1
Order By: Relevance
“…On the other hand, heterogeneity among members contributed to tensions, exacerbated internal conflicts, lowered levels of participation, and created delays in the fruition of policies. Divisiveness that accompanied diversity was particularly noted in the nursing literature [67,[80][81][82][84][85][86][87][88][89].…”
Section: Factors Influencing Priority Setting and Policy Advocacymentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, heterogeneity among members contributed to tensions, exacerbated internal conflicts, lowered levels of participation, and created delays in the fruition of policies. Divisiveness that accompanied diversity was particularly noted in the nursing literature [67,[80][81][82][84][85][86][87][88][89].…”
Section: Factors Influencing Priority Setting and Policy Advocacymentioning
confidence: 99%
“…Both bodies of literature reported that the inclusion of members in policy decisions and actions ensured selected policy issues had meaning for the public served [26,48,76,[90][91][92] and for members [16,36,37,85,86,90,92,93]. Members were also viewed as critical to the work accomplished by organizations, as they served as champions for their organizations' cause(s) [48,82,94].…”
Section: Factors Influencing Priority Setting and Policy Advocacymentioning
confidence: 99%
See 3 more Smart Citations